2018
DOI: 10.22598/mt/2018.30.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Influence on Parental Purchase Decisions: Typology of Innovative Products

Abstract: Purpose -There is common agreement that children's infl uence on parents to purchase products depends on the product category (products for a child vs. products for the family; minor everyday purchases vs. shopping goods). However, purchasing an innovative product in the presence of an adolescent, compared to the purchase of traditional products, creates a special context in which an adolescent might be considered a substantial source of expertise with diverse levels of impact on parents. The current research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Although this model is sometimes disparaged by researchers for not considering all possible purchase occasions (all five steps are not involved in every purchase situation like instant or impulsive purchase), hence the purchase decision process is affected by more complex influences (Arutselvi, 2012) and well demarcates grounding idea of the purchase process flow (Dikcius et al , 2018). The model is used to assess the role of children in the family buying process (Norgaard et al , 2007).…”
Section: Literature Review and Research Objectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this model is sometimes disparaged by researchers for not considering all possible purchase occasions (all five steps are not involved in every purchase situation like instant or impulsive purchase), hence the purchase decision process is affected by more complex influences (Arutselvi, 2012) and well demarcates grounding idea of the purchase process flow (Dikcius et al , 2018). The model is used to assess the role of children in the family buying process (Norgaard et al , 2007).…”
Section: Literature Review and Research Objectivesmentioning
confidence: 99%
“…Several studies have indicated children have a certain influence on family decision-making, other studies suggested children have little influence over how much to spend, where to make the purchase and the final decision (Wang et al , 2004). Interaction between parents and children are influenced by their personality characteristics (Dikcius et al , 2018), due to which parent-child combo is found to disagree in their perceptions regarding children’s influence in the purchase of specific products, as well as general influence in family decision processes (Foxman et al , 1989). Parents will allow less involvement of children for products in which they have sufficient expertise, and the children’s involvement in the purchase decision is subject to parents’ parents’ susceptibility to interpersonal influence (Dikcius et al , 2018).…”
Section: Literature Review and Research Objectivesmentioning
confidence: 99%
See 3 more Smart Citations